Skin and mucosal telangiectatic lesions in hereditary hemorrhagic telangiectasia patients. (6th July 2022) - Hyldahl, Stefanie J.; El‐Jaji, Mounir Q.; Schuster, Annette; Kjeldsen, Anette Drøhse
Abstract: Background: The diagnostic criteria for hereditary hemorrhagic telangiectasia (HHT) include the presence of telangiectatic lesions in common sites (nose, fingers, oral cavity, and lips). Telangiectatic lesions are described as red spots in the skin, but this description is inadequate. Few studies have investigated the characteristics of telangiectatic lesions in HHT, and we aimed to describe the distribution and morphology of telangiectatic lesions in HHT patients. Methods: We reviewed the telangiectatic lesions in 34 adult HHT patients seen at our HHT center. Photo documentation was used to describe the morphology and distribution of the lesions. Results: The telangiectatic lesions in both HHT1 and HHT2 patients were predominantly round and either flat or slightly elevated. However, elongated flat lesions and larger round, elevated lesions were also observed. Patients with HHT1 had more lesions in the mucosa (tongue and oral cavity) compared with HHT2 patients. There was no difference between HHT1 and HHT2 patients in the total number of lesions in the skin and mucosa. Conclusions: The typical round, flat telangiectatic lesion is the most common lesion in HHT, but it is very often accompanied by elevated or elongated lesions. The total number of lesions did not vary between gender, but women had significantly more lesions in the mucosa ( p = 0.027). The presentation of telangiectatic lesions may vary a little between HHT1 and HHT2 patients but not in such a way that allows the morphology and location of the lesions to predict the HHT subtype.